Proceso de ASC - APLICACIONES DE SISTEMAS DE REALIDAD VIRTUAL E INTELIGENCIA ARTIFICIAL PARA EL PROCESO DE VISUALIZACION Y CORPORIFICACION EN EL DISEÑO DE PRODUCTOS (2023)
DIGITAL TRANSFORMATION FOR PRODUCT DESIGN: Augmented reality (AR), virtual worlds (VR) and software and applications mediated by Artificial Intelligence (AI), share the common objective to help create built environments based on emotions, sensations and human connection. Between ideas of increase and immersion, many times these projects have been created in the hands of specialists from various fields of technology; At the same time, they represent a great opportunity for the training of future professionals. From what is described; This project aims identify and establish possibilities for the use of AI + VR + Virtual Environments focused on the application in Engineering Design processes; starting through the Product Design Engineering program. The project has the support from teachers of the program in question (IDP); which coordinate different subjects of the Visualization (Drawings) and configuration line or product embodiment (CAD modeling); with experience in these processes within the School of Applied Sciences and Engineering. As engineers, architects and designers develop new tools for the metaverse for example, as well as products, spaces virtual and augmented, new projects are increasingly democratized and collaborative; and at the same time, the creative and production process is being reinvented. design in different areas and professions. The use of these tools, software and applications mediated or assisted by Artificial Intelligence, represent an ethical debate and at the same time a challenge not only for education, but also as part of helping a creative process or faster design and with the possibility of more innovative results and innovative; since its implementation will occur sooner rather than later and know how to use and apply them correctly; They are part of the approach of this project.